Comparison of Consistency Value of Absorbent Dose of Plastisin and Silicone Bolus Using Electron With 6 Mev Energy at Sanglah Rsup Denpasar - Made Dwipa Nararta; Putu Eka Juliantara; Cory Amelia (International Journal Labs, 2022)
Background: Radiotherapy is a modality in the medical field that plays a role in the treatment of malignancy by utilizing ionizing rays by giving a lethal dose to cancer cells by causing minimal damage to normal cells. Objective: related research is to know the comparison of the consistency of the absorbed dose of the two materials at an energy of 6 MeV. Methods: used research with descriptive quantitative data processing to compare the consistency of the absorption dose values for boluses made from plasticine and boluses made from silicon at 6 MeV energy. To determine the consistency of the value of the absorption dose of boluses made of plasticine and silicone with a thickness of 1 cm each. Results: The results obtained the value of the absorbed dose which the value varies every day. Where for the absorption dose of bolus made from plasticine, the absorption dose ranges from 1.390 Gy to 1.413 Gy, with the average deviation percentage being 0.15%.